A case of resolution of inferior wall myocardial infarction and varying degrees of atrioventricular block: a case report - Kant, Priyesh; Singh, Prem Shanker; Kumar, Granth; Zafar, Khwaja Saifullah (International Journal of Research in Medical Sciences, 2017)
Inferior wall myocardial infarction (IWMI) complicating with high degree atrioventricular (AV) block had been a subject of discussion for a long time. Also the transient nature of these AV blocks in the presence of IWMI is well known to us. However our case presented with IWMI with right ventricular MI (RVMI) and in complete heart block and subsequently post thrombolysis developed varying degrees of AV block and reverted back to sinus rhythm. We found it as an incidence not much reported and thus reporting the case herewith.